An innovative service quality evaluation and improvement model. Issue 3 (12th March 2018) - Chen, Li-Fei; Chen, Szu-Chi; Su, Chao-Ton
ABSTRACT: Importance-performance analysis (IPA) is a popular approach used by firms to focus resources on crucial attributes, reduce expenditure on non-critical ones and develop improvement and innovation strategies accordingly. However, IPA develops quality improvement plans based on inaccurate assumptions about the independence between importance and performance and lacks clear measurement standards, which may lead to inappropriate recommendations. IPA also does not account for desired versus adequate service. Therefore, this study proposes an innovative framework that integrates the advantages of IPA, the zone of tolerance concept, and Kano's model. A case study conducted in a wealth management department in the banking industry demonstrates the effectiveness of the proposed methodology. The results indicate that the proposed approach recommends optimal service strategies to managers and outperforms traditional IPA.